Bennet's doubler working as a power booster for triboelectric nano‐generators. Issue 6 (1st March 2018) - Ghaffarinejad, A.; Lu, Y.; Hinchet, R.; Galayko, D.; Hasani, J.Y.; Kim, S.W.; Basset, P.
Abstract : In this Letter, the authors introduce for the first time how a Bennet's doubler conditioning circuit will boost the extracted energy from an electrostatic kinetic energy harvester based on triboelectricity. With zero initial bias on all capacitors, after 1000 charging cycles, the harvested power is amplified by more than 2 orders of magnitude by the Bennet's doubler in comparison to a half‐wave diode bridge. The harvested energy derived from a 3 × 3 cm 2 device made of polymer PFA and aluminium is at least 4.6 μJ per tap with the Bennet's doubler conditioning circuit, and only 30 nJ per tap with the half‐wave bridge.